Autophagy in cancer resistance to paclitaxel: Development of combination strategies - Škubník, Jan; Svobodová Pavlíčková, Vladimíra; Ruml, Tomáš; Rimpelová, Silvie (Biomedicine & pharmacotherapy, 2023)
Paclitaxel, a compound naturally occurring in yew, is a commonly used drug for the treatment of different types of cancer. Unfortunately, frequent cancer cell resistance significantly decreases its anticancer effectivity. The main reason for the resistance development is the paclitaxel-induced phenomenon of cytoprotective autophagy occurring by different mechanisms of action in dependence on a cell type and possibly even leading to metastases. Paclitaxel also induces autophagy in cancer stem cells, which greatly contributes to tumor resistance development. Paclitaxel anticancer effectivity can be predicted by the presence of several autophagy-related molecular markers, such as tumor necrosis factor superfamily member 13 in triple-negative breast cancer or cystine/glutamate transporter encoded by the SLC7A11 gene in ovarian cancer. Nevertheless, the undesired effects of paclitaxel-induced autophagy can be eliminated by paclitaxel co-administration with autophagy inhibitors, such as chloroquine. Interestingly, in certain cases, it is worthy of potentiating autophagy by paclitaxel combination with autophagy inducers, for instance, apatinib. A modern strategy in anticancer research is also to encapsulate chemotherapeutics into nanoparticle carriers or develop their novel derivatives with improved anticancer properties. Hence, in this review article, we summarize not only the current knowledge of paclitaxel-induced autophagy and its role in cancer resistance but mainly the possible drug combinations based on paclitaxel and their administration in nanoparticle-based formulations as well as paclitaxel analogs with autophagy-modulating properties.
Keywords: Nanoparticles; Humans; Antineoplastic Agents, Phytogenic; Drug co-administration; Autophagy markers; fytogenní protinádorové látky; Mitotic poisons; Female; nádory vaječníků; Ovarian Neoplasms; lidé; chemorezistence; autofagie; apoptóza; Cell death; Taxol; ženské pohlaví; paclitaxel; nádorové buněčné linie; Paclitaxel; Cell Line, Tumor; Autophagy; Drug Resistance, Neoplasm; Apoptosis